Face Threats in Threads: Assessing the Responses to Impoliteness in Facebook Comments on 1MDB - Ismail, Isma Noornisa; Shanmuganathan, Thilagavathi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Impoliteness has become common among online users and appears to be consented by netizens. This study seeks to investigate the reaction to impoliteness from the perspective of face-threat witnesses (FTWs) in Facebook comments. Twelve news posts on Facebook regarding the 1MDB scandal in 2015 were selected, and impolite comment threads that were reactions to the news were extracted. Fifty-two threads were found to contain impolite comments targeted at non-participants of this interaction, thus corresponding to the characteristics of face-threat witnesses. Dobs and Blitvich's (2013) model for participant response options, Culpeper's (2011, 2016) Conventionalised Impoliteness Formulae (CIF) and Bousfield's (2007) list of defensive counter-strategies were used to analyse the responses. Impolite responses by the FTWs were found to be atypical. Denying the opposition either via being offensive or defensive subjugated the preference in the findings, though offensive appeared more prominently. Apart from deny opposition, corroborate opposition, and react, the current study also discovered new categories for the response options which did not fit in any of the categories, hence labelled as Distinct Features. The FTWs not only sanctioned impoliteness, but initial impoliteness in their responses, despite being 'other-directed'. © 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.